2019
DOI: 10.3390/su11205721
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Family Involvement on Family Firm Internationalization: The Moderating Effects of Industrial and Institutional Environments

Abstract: This paper aimed to explore the effects of family ownership and management on Chinese family firm internationalization, and to examine the moderating effects of environmental munificence, institutional environment, and political ties in this relationship. A questionnaire survey of 274 family firms in 8 provinces or municipalities in China was conducted to test the proposed hypotheses empirically. The results were as follows: First, family ownership and management positively impacted the depth and breadth of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Some authors have documented a positive relationship with export intensity (Zhara, 2003;Chen et al, 2014;Cho and Lee, 2017;Marin et al, 2017;Zhou et al, 2019). Both Zahra (2003) and Marin et al (2017) support the stewardship theory, having found that family involvement in the ownership of a firm improves the performance of the internationalisation process because the family members see this strategy as a way to ensure the long-term sustainability of the company and obtain nonfinancial goals (SEW).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some authors have documented a positive relationship with export intensity (Zhara, 2003;Chen et al, 2014;Cho and Lee, 2017;Marin et al, 2017;Zhou et al, 2019). Both Zahra (2003) and Marin et al (2017) support the stewardship theory, having found that family involvement in the ownership of a firm improves the performance of the internationalisation process because the family members see this strategy as a way to ensure the long-term sustainability of the company and obtain nonfinancial goals (SEW).…”
Section: Introductionmentioning
confidence: 91%
“…Cho and Lee (2017) reach the same conclusion, drawing on resource-dependent theory and agency theory; they show that Korean SMEs with high family ownership accumulate strategic capabilities and resources and exploit agency benefits that favour export performance. Zhou et al (2019) show that family ownership is a special resource that can provide family firms with the needed resources for internationalisation, such as family human capital, social capital, patient capital and survivability capital. In contrast, other researchers have found a negative relationship between family firms and export performance Nieto, 2005, 2006;Ray et al, 2018), showing that the disadvantages of family ownership outweigh the benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Two dimensions of family involvement (i.e., family involvement in ownership and family involvement in management) can be distinguished on the basis of the existing literature [78][79][80][81]. Family involvement in ownership depicts the degree of family ownership and intrafamily ownership dispersion, while family involvement in management indicates the presence of the family members in the management teams of the company [78,79].…”
Section: Family Involvement and Proactive Ecsrmentioning
confidence: 99%
“…Then the difference between them becomes extremely significant when the leading firms and the focal affiliate are located in different regions or provinces. It is because the industry and institutional environment varies across provinces and more variations could be found by comparing the eastern region with the western region of China (Zhou, 2019). More variations will lead to bigger difference between the intra-group system and the out-group system in the local city where the focal affiliate operates.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%